The law of possession: ritual, healing, and the secular state - Sax, William Sturman; Basu, Helene (Oxford University Press, 2015)
Machine generated contents note: -- 1. The Law of Possession: Ritual, Healing, and the Secular State, William S. Sax and Helene Basu -- 2. In the Courtroom of Jungle Saints: The Poor and Transcendental Justice, Helene Basu -- 3. Between Shrine and Courtroom: Legal Pluralism, Witchcraft, and Spirit Agency in South-Eastern Africa, Arne S. Steinforth -- 4. Delocalizing Illness: Healing and the State in Chinese Medicine, Dominic Steavu -- 5. Justice in Erwadi: A Case Study, Bhargavi Davar -- 6. Possession and the Anti-Superstition Law in Maharashtra: An Actors' Perspective on Modernization and Disenchantment, Johannes Quack -- 7. "If your brother wants to kill you, kill him first": Healing, Law, and Social Justice in an African Healer's Courtroom, Ferdinand Okwaro -- 8. The Darbar of Goludev: Possession, Petitions, and Modernity, Aditya Malik -- 9. Gods of Justice, William S. Sax -- Index